Adjustment costs of monetary integration in CARICOM - Bennett, Karl M. (ISER MonaJA, 1993)
Reviews the theoretical approaches adopted for assessing the costs of participating in a monetary union. Looks at the use of instruments of macroeconomic policy in Barbados, Guyana, Jamaica & Trinidad and Tobago over the decade of the eighties. Attempts to derive estimates of the potential costs to the economies of Guyana, Jamaica, Trinidad and Tobago of having to forego control over the use of fiscal, monetary and exchange rate policy.